Mexican Hat Net used to increase the security of encoded text - Maha Al-Badrani (College of Education for Pure Sciences, 2010)
ABSTRACT The interactive with information considers a large problem specially in transformation of information that need a top security and storage. Therefore, it was necessary using the artificial neural network ,that consider from the modern application in artificial intelligent, if it dependent on biological bases in simulation human behavior. This search dependent on the idea of cipher by the use of decimated alphabet cipher and for the purpose of increasing the security of cipher data ,the feed is done on the artificial neural network, which is the (Mexican Hat Net) to enter the cipher text for the purpose of increasing the security of the text and then decipher. The result provide the ability of ciphering by using the decimated alphabet cipher method with Mexican Hat Net and then decipher and checked the correct of the results in the operation of decipher keeping on the security of these cipher data from hackers by this algorithm.